Correlated Proportions Test under Indeterminacy - Abdullah M. Almarashi; Muhammad Aslam (Journal of Mathematics)
The existing Z-test for correlated proportions under classical statistics is applied when observations in the data are exact and precise. In the current paper, Z-test for correlated proportions is proposed to deal with the data having indeterminate observations. The statistic of Z-test for correlated proportions under neutrosophy is introduced in the paper. The testing procedure of the proposed test is given. The application of the proposed test is given using the price of oil data. From the application, it is clear that the proposed test outperforms the existing Z-test for correlated proportions under classical statistics in terms of flexibility, adequacy, and information. The simulation study also shows the effect of indeterminacy on the statistic of the proposed test.